Razvoj molekularne baze podatkov za smreko in možnost razlikovanja treh provenienc na podlagi molekularnih markerjev - Westergren, Marjana (Gozdarski vestnik, 2005)
The introductory development of molecular databases with STS and EST DNA markers is presented on the example of 3 provenances of Norway spruce (Leskov grm, Hrušica, Konačnik). The selected DNA markers proved to be potentially suitable for the discrimination of provenance regions. However, analyses of more samples are needed throughout Slovenia to confirm the existing ecologically based delineation of provenance regions. Expanding the database with the use of more polymorphic markers is necessary to increase the capability of discriminating between different provenances and individuals.
Keywords: baze podatkov; genetika; Picea abies L.; reprodukcijski material; smreka